MYD88 Is a Potential Prognostic Gene and Immune Signature of Tumor Microenvironment for Gliomas - Guo, Qinglong; Xiao, Xing; Zhang, Jinsen (Frontiers in Oncology, 2021)
Purpose To explore the profiles of immune and stromal components of the tumor microenvironment (TME) and their related key genes in gliomas. Methods We applied bioinformatic techniques to identify the core gene that participated in the regulation of the TME of the gliomas. And immunohistochemistry staining was used to calculate the gene expressions in clinical cases. Results We applied CIBERSORT and ESTIMATE algorithm to calculate the composition of TME in 698 glioma cases from TCGA database. Differential expression analysis was employed to identify 2103 genes between the high-score group and the low-score group, which were utilized to conduct Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) enrichment analysis. The differentially expressed genes (DEGs) were analyzed by COX regression analysis and protein–protein interaction (PPI) network construction. Then, MYD88 was identified as a predictive factor by the intersection analysis of univariate Cox and PPI. Further analysis revealed that MYD88 expression was correlated with the overall survival and WHO grade of glioma patients. Gene Set Enrichment Analysis (GSEA) showed that the genes in the high-expression MYD88 group were mainly enriched in immune-related activities. We found that macrophage M2 accounted for the largest portion with an average of 27.6% in the glioma TIICs and was associated with high expression of MYD88. The results were verified in CGGA database and clinical cases in our hospital. Furthermore, we also found the MYD88 expression was higher in IDH1 wild types. The methylation rate was lower in high grade gliomas. Conclusion MYD88 had predictive prognostic value in glioma patients by influencing TIICs dysregulation especially the M2-type macrophages.